Real-time deformability cytometry reveals sequential contraction and expansion during neutrophil priming - Bashant, Kathleen R.; Vassallo, Arlette; Herold, Christoph; Berner, Reinhard; Menschner, Leonhard; Subburayalu, Julien; Kaplan, Mariana J.; Summers, Charlotte; Guck, Jochen; Chilvers, Edwin R.; Toepfner, Nicole (Journal of Leukocyte Biology, 2019)
It has become increasingly apparent that the biomechanical properties of neutrophils impact on their trafficking through the circulation and in particularly through the pulmonary capillary bed. The retention of polarized or shape-changed neutrophils in the lungs was recently proposed to contribute to acute respiratory distress syndrome pathogenesis. Accordingly, this study tested the hypothesis that neutrophil priming is coupled to morpho-rheological (MORE) changes capable of altering cell function. We employ real-time deformability cytometry (RT-DC), a recently developed, rapid, and sensitive way to assess the distribution of size, shape, and deformability of thousands of cells within seconds. During RT-DC analysis, neutrophils can be easily identified within anticoagulated “whole blood” due to their unique granularity and size, thus avoiding the need for further isolation techniques, which affect biomechanical cell properties. Hence, RT-DC is uniquely suited to describe the kinetics of MORE cell changes. We reveal that, following activation or priming, neutrophils undergo a short period of cell shrinking and stiffening, followed by a phase of cell expansion and softening. In some contexts, neutrophils ultimately recover their un-primed mechanical phenotype. The mechanism(s) underlying changes in human neutrophil size are shown to be Na+/H+ antiport-dependent and are predicted to have profound implications for neutrophil movement through the vascular system in health and disease.
CRIS-Team Scopus Importer:2022-08-05
Keywords: macropinocytosis; morpho-rheological (MORE) phenotyping; neutrophil priming and de-priming